Fotoativas a base de imidiazolatos de imidiazolatos para degradação do fármaco ciprofloxacina - SANTOS, Wemerson Daniel Correia dos (2022)
Currently, many researchers are carried out looking for alternatives for the treatment of water. A promising alternative is through photocatalysis, a process based on the oxidation of organic species through light in the ultraviolet or visible region, where the search for materials with good photocatalytic activity is increasing. Thus, the use of zeolitic imidazolate-like structures, such as the ZIF-8 structure, becomes interesting, since it has a high surface area, good adsorptive capacity and the presence of metallic sites such as Zn, which can provide good, interesting properties. photocatalytic. Such material can combine with other porous inorganic structures such as zeolite sodalite and lamellar alkali silicate magadiite, forming heterostructured materials with improved properties compared to their separate components. Based on these premises, the present dissertation is focused on the in situ synthesis of ZIF-8 in the presence of sodalite and magadiite solids, forming heterostructured materials. The formation of zeolitic imidazolate in the presence of zeolite and lamellar silicate was confirmed by XRD through reflections of ZIF-8 in the heterostructures, also showing good thermal stability as indicated by TG/DTA analyses. The possible interactions between both inorganic phases were evidenced by FTIR where it was possible to observe bands referring to the organic ligand. Through heat treatment of the previously formed heterostructure, it was possible to obtain a surface enriched with ZnO from the ZIF-8 fraction, which was confirmed by XRD. Furthermore, through SEM images, it was possible to observe the characteristic morphology of both materials and analyze the average size distribution of the synthesized particles. Such materials were used in photocatalytic assays of degradation of the drug Ciprofloxacin, where it was observed that the heterostructure formed with ZIF-8 and sodalite presents a good photocatalytic performance using ultraviolet radiation, presenting 65% of photodegradation. However, a superior performance was revealed for those materials submitted to heat treatment and consequent formation of ZnO. The ZnO/SOD presenting a degradation rate of approximately 98% in 120 min of test.